O Papel dos profissionais de gestão de pessoas no processo de inclusão de pessoas com deficiência no mercado de trabalho na cidade de São Luis - MA - Maciel, Júlio César Pinheiro (2010)
The inclusion of people with disabilities is a challenge for organizations and for people with disabilities who want a job where they can have their rights respected and safeguarded. In this process the professional management of people has an important role in making the environment accessible to all, to map the positions and jobs, raise awareness of the company, empowering managers to minimize the impact of integration into work environments and field Tools of hiring professionals with disabilities, validating the inclusion program, and training of professionals with disabilities. This work aims to investigate whether the professional management of people are ready for the challenge to deploy and develop internal policies to include people with disabilities in businesses in which they operate. For this, we made a survey of professionals responsible for programs for inclusion in companies with more than 1,000 employees in the municipality of São Luís - MA, to evaluate the practices adopted by organizations.